Innovations and policy design for development for cross-value chain services (logistics and financial services) - Balana, Bedru; Olanrewaju, Opeyemi; Ambler, Kate; de Brauw, Alan; Bloem, Jeffrey R.; Kadjo, Didier; Wossen, Tesfamichael; Liverpool-Tasie, Saweda Lenis Onipede; Abdoulaye, Tahirou (International Food Policy Research Institute, 2022)
WP3 intends to address the question: How can cross-food value chain and market services function better to increase employment and boost income of smallholders and SMEs? The WP focuses on two types of cross-value chain services, logistics and financial services. (1) logistics services – supply chain management, transportation, traceability, digital platforms for e-com merce, and (cold) storage. (2) value-chain financial services – mainly focusing on digital financial services (DFS) that facilitate trans actions, savings, access to and use of credit, and insurance. The logistics services in agri-food systems in low- and middle-income countries (LMICs) are often targeted at large-scale enterprises with greater market power and less accessible to smallholder farmers and small and micro enterprises (SMEs). WP3 aims to assess the ways in which these emerging logistics services (including digital platforms) can be cost-effectively targeted at smallholder farmers and agri-food SMEs. Regarding DFS, the WP will investigate cost-effective ways of improving access to and adoption of DFS among smallholders and agri-food SMEs, especially among women and youth. Though these emerging DFS appear to have a high potential to benefit smallholders and SMEs across the agri-food value chains in LMICs, they need a reliable internet connection, a suitable mobile phone network, and a broad network of mobile money agents to be effective. WP3 thus aims to identify innovations/emerging logistics and DFS and test their effectiveness to smallholders and SMEs using randomized control trials (RCTs) in pilots, with the goal of country-specific scalable designs.